DISEMINASI INFORMASI KESEHATAN MENTAL “BUILD MENTAL SHINE MORE” PADA MASYARAKAT USIA 17-45 TAHUN MELALUI PLATFORM YUK BERDIALOG DENGAN TEORI DIFUSI INOFASI - Reformanda, Chrisindo; Paul, Kezia Melasari (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
The webinar “Build Mental, Shine More” was organized by the yukberdialog platform with the aim of improving participants' understanding of mental health and stress management. This study evaluates how new ideas about mental health are introduced and adopted by participants through the diffusion of innovation theory approach. Using various communication channels such as social media and email, the webinar successfully disseminated relevant and practical information on stress management, healthy eating, and the importance of social support. Results showed that the relative advantage, trialability, and observability of mental health strategies contributed to their rapid adoption by participants. The webinar served as an effective model for applying diffusion of innovations theory to promote mental health in academic and professional settings.